How to solve and answer
![How to solve and answer class=](https://us-static.z-dn.net/files/d5f/7ac560fc09ba4fd10745ef9c9898592a.png)
Answer:
D. (-2, 0) and (3, 0).
Step-by-step explanation:
At the x -intercepts the function = 0, so
(2x + 4)(x - 3) = 0
2x + 4 = 0 and x - 3 = 0
x = -4/2 = -2 and x = 3.
So they are (-2, 0) and (3, 0).
x = 3 or x = -2
Step-by-step explanation:
f(x) = (2x + 4)(x - 3)
y = (2x + 4)(x - 3)
x - intercept occurs when y = 0
0 = (2x + 4)(x - 3)
0 = 2x² - 6x + 4x - 12
2x² - 2x - 12 = 0
(2x² - 2x - 12)/2 = 0/2
x² - x - 6 = 0
From the quadratic formula,
x = (-b +- √(b² - 4ac))/2a
x = (- ( -1 ) +- √(( -1)² - 4( 1 )( -6 )))/2( -1 )
x = (1 +- √(1 - ( -24)))/-2
x = (1 +- √25)/-2
x = (1 +- 5)/-2
x = 3 or x = -2